How a Multinational Company Builds Supply-Chain Resilience through Proactive and Reactive Strategies in a Customized, Resource-Intensive Industry - Hallila, Jukka (2025)
Companies that manufacture customized resource-intensive products have structural weaknesses in their supply chain design: the engineer-to-order production model, single sourcing of components, and long transportation times. In this context, supply chain resilience requires more than standardized supply chain planning. This thesis explores how a multinational company in the customized, resource-intensive industry builds its supply-chain resilience through proactive and reactive strategies.